Downregulation of astroglial glutamate transporter GLT-1 in the lateral habenula is associated with depressive-like behaviors in a rat model of Parkinson's disease. (15th September 2021) - Lyu, Shuxuan; Guo, Yuan; Zhang, Li; Tang, Guoyi; Li, Ruotong; Yang, Jie; Gao, Shasha; Li, Wenjuan; Liu, Jian
Abstract: Recent studies show that neuron-glial communication plays an important role in neurological diseases. Particularly, dysfunction of astroglial glutamate transporter GLT-1 has been involved in various neuropsychiatric disorders, including Parkinson's disease (PD) and depression. Our previous studies indicated hyperactivity of neurons in the lateral habenula (LHb) of hemiparkinsonian rats with depressive-like behaviors. Thus, we hypothesized that impaired expression or function of GLT-1 in the LHb might be a potential contributor to LHb hyperactivity, which consequently induces PD-related depression. In the study, unilateral lesions of the substantia nigra pars compacta (SNc) by 6-hydroxydopamine in rats induced depressive-like behaviors and resulted in neuronal hyperactivity as well as increased glutamate levels in the LHb compared to sham-lesioned rats. Intra-LHb injection of GLT-1 inhibitor WAY-213613 induced the depressive-like behaviors in both groups, but the dose producing behavioral effects in the lesioned rats was lower than that of sham-lesioned rats. In the two groups of rats, WAY-213613 increased the firing rate of LHb neurons and extracellular levels of glutamate, and these excitatory effects in the lesioned rats lasted longer than those in sham-lesioned rats. The functional changes of the GLT-1 which primarily expresses in astrocytes in the LHb may attribute to its downregulation after degeneration of the nigrostriatal pathway. Bioinformatics analysis showed that GLT-1 is correlated with various biomarkers of PD and depression risks. Collectively, our study suggests that astroglial GLT-1 in the LHb regulates the firing activity of the neurons, whereupon its downregulation and dysfunction are closely associated with PD-related depression. Highlights: Blockade of LHb GLT-1 induced depressive-like behaviors in sham and SNc lesioned rats. GLT-1 inhibitor enhanced the firing rate of LHb neurons in both groups of rats. GLT-1 inhibitor increased LHb glutamate levels in both groups of rats. The lesioned rats were more sensitive to the GLT-1 blockade compared to sham rats. Astroglial GLT-1 was down-regulated in the LHb after lesioning the SNc.